Why human rights matter for marine conservation - Smallhorn-West, Patrick; Allison, Edward; Gurney, Georgina; Karnad, Divya; Kretser, Heidi; Lobo, Aaron Savio; Mangubhai, Sangeeta; Newing, Helen; Pennell, Kamille; Raj, Sushil; Tilley, Alexander; Williams, Haley; et al. (Frontiers in Marine Science, 2023)
Why are human rights important to marine conservation? Marine conservation is fundamentally about how people interact with the environment, hence social and environmental issues are inextricably linked. While the field of marine conservation is increasingly considering human well-being, it retains a legacy of protectionism, colonialism, and fortress conservation. Here, we i) provide an overview of human rights principles and how they relate to marine conservation, ii) document cases where tensions have occurred between conservation goals and human rights issues, iii) review the legal and ethical obligations, and practical benefits, for marine conservation to support human rights, and iv) provide practical guidance on integrating human rights principles into marine conservation. We argue that adopting a human rights-based approach to marine conservation, that is a reframing of equity from a charitable principle to a right-based condition, will not only help meet obligations to respect, protect, and fulfil human rights, but will also result in greater and more enduring conservation impact.